A Kinetic Model for Tribological Surface Transformations Occuring on the Railroads: Irreversible Near-Surface Metallurgical Transformations. (1st November 2012) - Antoni, G.
Abstract : During the manufacturing processes or the operational phases, some materials are liable to undergo metallurgical phenomena known as irreversible solid-solid phase transformations or Tribological Surface Transformations (TSTs). The treads of several rails in the French railroad network have been affected by TSTs. The kinetic model presented in this paper describes the initiation of TSTs and their development near the rail surface.